Prevalence and Risk Factors of Hypertension Among Diabetic Patients - Haidari, Said Rahatullah; Haidary, Said Qamber Ali (Journal for Research in Applied Sciences and Biotechnology, 2024)
Hypertension poses a significant public health concern, leading to increased morbidity and mortality rates. Its coexistence with diabetes often worsens the complications associated with both conditions. The aim of this study was to examine the prevalence of hypertension and the factors influencing its occurrence among diabetic patients receiving follow-up care at the Haidari Internal Medicine, Gastrointestinal Diseases, GI Endoscopy, and Colonoscopy Center in Jalalabad city, Nangarhar Province, Afghanistan. The study was carried out from November 1, 2023, to January 30, 2024. We utilized a cross-sectional design and conducted statistical analysis using SPSS software version 25.0. Categorical data were expressed as frequencies and percentages. The associations between hypertension and various variables in diabetes mellitus (DM) were evaluated using chi-square tests for trend. The findings demonstrated that age ≥ 50 years, higher BMI, and type 2 DM were significant predictors of hypertension among the studied population. Additionally, illiteracy, active smoking, a family history of hypertension, physical inactivity, having diabetes for 5 or more years, and using both non-insulin and insulin treatments were linked to a higher prevalence of hypertension. These findings highlight the need to address these risk factors in the management and prevention of hypertension among individuals with diabetes.